Speech at Maternal, Newborn and Child Health Summit, Toronto, Canada, May 30, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, notes that we stand at a critical threshold for global health and development. Too many women and children are still dying because they lack access to quality health care, especially in the least developed countries. He talks about shifting focus from inputs to paying for results, an approach that has been proven to be extremely effective in getting high quality, essential health services to women and children. He remarks that empowering frontline health workers with the autonomy and resources to develop strategies to improve service delivery has resulted in transformational changes in access and quality. As countries move toward universal coverage, fewer mothers die in childbirth, and more babies are born healthy.